EVALUASI INVITRO AKTIVITAS ANTIOKSIDAN DAN TABIR SURYA DARI EKSTRAK DAUN DAN AKAR TUMBUHAN Elephantopus mollis Kunth - Verawati Verawati; Miftahur Rahmi; Intan Suci Mayasari (Jurnal Ilmiah Farmasi Farmasyifa, 2022)
Solar radiation in Indonesia is quite abundant because geographically it is located at equatorial latitudes, so people are vulnerable to feel the bad effects of solar radiation. Chemical components with antioxidant properties can also act as sunscreens to prevent the negative effects of solar radiation. This study aimed to determine the antioxidant and sunscreen activity of the leaf and root extract of the Tutup Bumi (Elephantopus mollis Kunth) plant. The antioxidant activity test was examined by the DPPH radical scavenging method (2,2-diphenyl-1-picrylhydrazyl) while the sunscreen potency was determined by calculating the SPF value using the Mansur method spectrophotometrically. The results of the examination showed that the antioxidant activity was quite strong, namely the leaf extract with IC50 79.38 g/mL and root extract 78.38 g/mL. The SPF value of the leaf extract is better than that of the root extract, where at a concentration of 500 ppm, the leaf extract has an SPF of 7.661 in the Extra category while the root extract at the same concentration has an SPF value of 5.176 in the Medium category. Tutup Bumi leaf and root extracts have potential as antioxidants and sunscreens.